2017
DOI: 10.1051/matecconf/201712502048
|View full text |Cite
|
Sign up to set email alerts
|

Impact behaviour of acrylonitrile-butadiene-styrene after temperature and humidity load

Abstract: Abstract. This study deals with acrylonitrile-butadiene-styrene (ABS) which was subjected the drop-weight test before and after temperature and humidity load. ABS is an engineering plastic and also an important engineering terpolymer, which has butadiene part uniformly distributed through the acrylonitrile-styrene matrix and is commonly used in production of automotive interior components. The injection moulded ABS samples were subjected the penetration test at fall height 100 J before and after temperature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Such blending, surprisingly, produces a PC/ABS blend which is combining the excellent impact resistance of PC and the ease of processing with low-temperature ductility of ABS [4]. Many studies reported that rubber content and its particle size contribute not only in increasing impact strength and toughness of AS or SAN [5] but also in improving notch-sensitivity and durability of PC [6][7][8]. In a study on the effect of rubber content in ABS on PC/ABS blends, Tan et al [9] reported that with increase in the contents of rubber up to 30 wt%, the impact strength of the PC/ABS blends was promptly improved and then, however, subsequently decreased for higher contents of rubber.…”
Section: Introductionmentioning
confidence: 99%
“…Such blending, surprisingly, produces a PC/ABS blend which is combining the excellent impact resistance of PC and the ease of processing with low-temperature ductility of ABS [4]. Many studies reported that rubber content and its particle size contribute not only in increasing impact strength and toughness of AS or SAN [5] but also in improving notch-sensitivity and durability of PC [6][7][8]. In a study on the effect of rubber content in ABS on PC/ABS blends, Tan et al [9] reported that with increase in the contents of rubber up to 30 wt%, the impact strength of the PC/ABS blends was promptly improved and then, however, subsequently decreased for higher contents of rubber.…”
Section: Introductionmentioning
confidence: 99%
“…PC/ABS blends, for instance, are the blends produced from blending ABS into PC to obtain the beneficial properties from both PC and ABS. Rubber content and its particle size in ABS contribute not only in increasing impact strength and toughness of ABS [1] but also in improving notch-sensitivity of PC [2][3][4]. In a study on the effect of rubber content in ABS on PC/ABS blends, Tan et al [5] reported that the impact strength of the PC/ABS blends promptly increased with increasing the rubber contents up to 30 wt% and then subsequently decreased for higher rubber contents.…”
Section: Introductionmentioning
confidence: 99%
“…In the past our team investigated the impact strength of ABS before and after humidity loading and also the crack growth. It was proved that after humidity loading ABS proved significantly lower impact resistance than before loading [Hylova 2017]. This study compares SAN and ABS in the mechanical behaviour point of view of these materials using drop-weight impact tester.…”
Section: Introductionmentioning
confidence: 99%